Constraints to Urban Planning and Management of Secondary Towns in Uganda - Amin Tamale Kiggundu (Indonesian Journal of Geography, 2014)
Many towns in Uganda are growing at an unprecedented rate. By 2030 more than 50% of Ugandans will beliving in urban centres. This rapid growth of urban centres in Uganda provides for economic opportunities for manyurban residents. It also poses various challenges such as urban sprawl, emergence of informal settlements as well asurban poverty. Over 60% of the urban residents in Uganda live in the informal settlements with no basic services andinfrastructure such as piped water, decent housing, good roads, sewerage systems as well as schools and health centres.This paper aims to examine and understand the constraints to urban planning and management of secondary towns inUganda. Using an eclectic mix of research methods such as face to face interviews targeting key informants, a questionnairesurvey as well as observation, the study found that the current modernist planning approach has not achieved itsintended goal of promoting orderly urban development and improve service delivery in the secondary towns. The studyalso revealed that the urban residents are rarely involved in planning. Besides, there is an apparent mismatch betweenwhat is taught at the local planning schools and what is required in terms of planning in the secondary towns. To addressthese intractable urban challenges, it is critical that the current planning education and curriculum are reviewed to producecreative and imaginative planners that can respond more effectively to the community problems, adopt a strategyto promote strategic spatial planning that is more participatory, carry out public awareness campaigns about the need forproper planning of towns and adopt a strategy for promoting innovative funding programmes such as municipal bonds,use of the stock exchange to mobilise the required investable funds, allow the private sector to access institutional fundssuch as the employee provident fund and promote public-private partnerships.